LINEAR AND SPATIAL CORRELATION BETWEEN BEAN YIELD AND PHYSICAL ATTRIBUTES OF A RED LATOSOL IN SELVÍRIA (MS, BRAZIL) - MONTANARI, RAFAEL; CARVALHO, MOREL DE P. E; SIQUEIRA, GLÉCIO M.; DAFONTE, JORGE; GONZÁLEZ, ANTONIO PAZ (Revista Brasileira de Engenharia de Biossistemas, 2009)
This work aimed to evaluate the soil physical attributes spatial variability concerning to the relationmass/volume (macro porosity, micro porosity, total porosity, and soil density) and beans fields (gainsyield) through the linear correlation and spatial variability analysis among cited attributes. Samplingwas done at an experimental field of UNESP/Ilha Solteira, SP, Brazil on an Oxisol under no-tillage soilmanagement and with irrigation during the cropping seasons of 2004/2005. The samples were collectedin 119 different points in one area of 0.99 ha. The total soil porosity (PT), macro porosity (MA), microporosity (MI), soil bulk density (SD) and beans yield (PG) showed low variability with spatial dependenceranges between 22.9 m and 77.9 m. The linear correlation between the soil attributes ranged fromnull to high. Correlation between grain yield and the soil physical attributes was null.